Importance of Social Support of Parents of Children with Cancer: A Multicomponent Model Using Partial Least Squares-Path Modelling - Melguizo-Garín, Ana Isabel; Benítez-Márquez, María Dolores; Hombrados-Mendieta, Isabel; Martos-Méndez, María José (IOAP-MDPI, 2023)
he purpose of the present study is to build a model combining some variables that have been previously studied separately to improve our understanding on how they relate in parents of children with cancer. A total of 112 parents with an average age of 41 completed the self-assessment questionnaires containing the factors studied: social support received, social support provided, stress, adjustment of parents and life satisfaction. Two models were developed: one for social support received and one for social support provided. Structural equation models based on the variance estimated through partial least squares were used to analyze factors involved in quality of life based on an exploratory model of second order. The estimated model was robust in terms of quality of measurement (reliability and validity). According to results from the structural model, in the model of social support received, the impact of social support received on stress was considerable (β = −0.26; p = 0.02) and it explained 16% of the variance. The impact of social support received by parents on their adjustment (β = −0.56; p < 0.001) was also considerable, explaining 32% of the variance. Finally, adjustment of parents also showed an effect on life satisfaction (β = −0.33; p < 0.001) and it explained 26% of the variance. However, the relation between social support received (β = 0.15; p = 0.11) and life satisfaction, the relation between stress (β = −0.15; p = 0.08) and life satisfaction, and the relation between adjustment of parents (β = 0.20; p = 0.07) and stress were not significant. In the model of social support provided by parents, social support provided (β = 0.35; p < 0.001), and adjustment of parents (β = −0.31; p < 0.01) impacted life satisfaction, explaining 36% of the variance. Social support provided (β = −0.34; p < 0.01) impacted adjustment of parents and it explained 12% of the variance. (...)
Keywords: Estrés (Fisiología); Social support received; Adjustment of parents; Stress; Life satisfaction; Parents of children with cancer; PLS-SEM; Structural equation modelling